1985
DOI: 10.1002/art.1780280214
|View full text |Cite
|
Sign up to set email alerts
|

Soluble mediators from mononuclear cells increase the synthesis of glycosaminoglycan by dermal fibroblast cultures derived from normal subjects and progressive systemic sclerosis patients

Abstract: Dermal fibroblast cultures from patients with progressive systemic sclerosis (PSS) synthesize up to 5 times more glycosaminoglycan (GAG) than normal cultures. In an in vitro model of fibroblast-lymphocyte interactions, we show that the supernatants of activated mononuclear cells (MNC) modulate GAG synthesis, as measured by the incorporation of 3H-glucosamine into GAG following incubation of the confluent fibroblast monolayers with active supernatant preparations. GAG accumulation was selectively increased up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

1985
1985
2007
2007

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…Under defined growth conditions and with a standard inoculum of 40,000 fibroblasts in the log phase of growth, normal and PSS cultures are in confluence by day 6 (16). Using strains, we have shown that no further increases in cell numbers occur by day 4 of culture (unpublished observations).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Under defined growth conditions and with a standard inoculum of 40,000 fibroblasts in the log phase of growth, normal and PSS cultures are in confluence by day 6 (16). Using strains, we have shown that no further increases in cell numbers occur by day 4 of culture (unpublished observations).…”
Section: Resultsmentioning
confidence: 85%
“…Fresh medium and supernatants of MNC not activated with Con A were used as controls. The fibroblasts were incubated with the MNC-SN for 72 hours (16) and then assayed for GAG accumulation as described below. Active MNC-SN were pooled and stored at -70°C until further use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These numbers were used to calculate the levels of GAG and CSP synthesis per cell. In each of the triplicate wells, GAG synthesis was estimated as the counts per minute of 'Hglucosamine incorporated into total GAG (cells + culture medium) and precipitable by cetylpyridinium chloride, as described previously (15). The CSP synthesis was determined in triplicate wells as the cpm of 3H-proline incorporated into total acid-soluble, collagenase-sensitive material, using the method of Peterkofsky and Diegelman (16), with our modifications as described elsewhere (17).…”
Section: Methodsmentioning
confidence: 99%
“…It is possible that a combination of selection and activation events could account for its appearance. A variety of mechanisms, including serum factors (6,22) and products of mononuclear cells (15,17,23), have been proposed as effectors of fibrotic changes in PSS and other diseases.…”
Section: Normal Clones Mitmentioning
confidence: 99%